2020
DOI: 10.1002/jmd2.12144
|View full text |Cite
|
Sign up to set email alerts
|

Early biochemical effects of velmanase alfa in a 7‐month‐old infant with alpha‐mannosidosis

Abstract: Alpha mannosidosis is an ultrarare pathology with variable phenotypic manifestations, characterized by the deficiency of lysosomal alpha mannosidase which causes accumulation of neutral oligosaccharides. Until recently, the hematopoietic stem cell transplantation was the only clinical feasible therapeutic option. Only in 2018, the European Medicines Agency's committee approved the recombinant enzyme velmanase alfa for long‐term treatment of non‐neurological manifestations in mild and moderate forms of alpha‐ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Man2GlcNAc trisaccharide was identified as the most abundant structure in all AM samples in accordance with literature data [19]. Previous studies have linked the ManOS levels to AM severity [12] and treatment response either by HSCT [35] or ERT [13]. During Phase I-II of clinical testing of rhLAMAN, Borgwardt et al [31] observed an over-all 54.1% decrease in urinary ManOS in 10 patients over 12 months.…”
Section: Evaluation Of Ert Efficacysupporting
confidence: 82%
See 4 more Smart Citations
“…Man2GlcNAc trisaccharide was identified as the most abundant structure in all AM samples in accordance with literature data [19]. Previous studies have linked the ManOS levels to AM severity [12] and treatment response either by HSCT [35] or ERT [13]. During Phase I-II of clinical testing of rhLAMAN, Borgwardt et al [31] observed an over-all 54.1% decrease in urinary ManOS in 10 patients over 12 months.…”
Section: Evaluation Of Ert Efficacysupporting
confidence: 82%
“…During Phase I-II of clinical testing of rhLAMAN, Borgwardt et al [31] observed an over-all 54.1% decrease in urinary ManOS in 10 patients over 12 months. Santoro et al [13] reported a 67% decrease in urinary ManOS in a 7-month-old infant after two months of ERT. In our work, we observed an 88.6% decrease in total urinary ManOS after four months of ERT.…”
Section: Evaluation Of Ert Efficacymentioning
confidence: 98%
See 3 more Smart Citations